Jabat Tangan Dengan Cium Tangan Kyai Untuk Keberkahan Dalam Perspektif Quran - Tammulis Tammulis; M. Galib M; Achmad Abubakar (Ulumuddin : Jurnal Ilmu-ilmu Keislaman, 2021)
This research is related to the source of the Koran regarding the culture of students who kiss the hands of clerics or scholars with the belief to get blessings (tabarruk). The are two formulations of the problem, namely what is the view of the Koran regarding the culture of shaking hands by kissing the hands of scholars or kyai? Can kissing the hands of scholars or kyai get blessings according to the Qur’an? This study uses verse analysis and interpretation of the Qur’an with the mauḍū’īy (thematic) interpretation method. As for the conclusion that kissing the hands of a cleric or cleric as a form is permissible in the Qur’an, even the Qur’an obliges to glorify the ulama. The handshake by kissing the cleric’s hand, according to the Qur’an, can invite blessings from Allah because in the Qur’an one of the things that causes blessings to come down for people who always greet and stay in touch. Even in the Qur’an it is stated that then ulama are those who fear Allah, and those who are pious according to the Qur’an will be blessed by Allah SWT.